PENGGUNAAN METODE ECONOMIC ORDER QUANTITY (EOQ) UNTUK MENGOPTIMALKAN BIAYA PERSEDIAAN PADA PT. ALPHACON VALFINDO - Bambang Pujo Purwoko; Lusiana Lusiana (The Asia Pacific Journal Of Management Studies, 2018)
PT. Alphacon Valfindo is a company engaged in manufacturing valve in Indonesia. For the production process, PT. Alphacon Valfindo requires raw materials for casting (the product). The most widely used raw material is Scrap. There are several problems in the control of scrap raw material inventory, among which is the purchase of raw materials with the amount that exceeds the needs of production. This leads to the accumulation of raw materials, thus causing storage costs to be free. To control the cost of inventory, this research uses Economic Order Quantity (EOQ) method to compare the average cost of inventory more optimally with the actual inventory cost of the company.This type of research used in this research is quantitative research using a descriptive approach. The population of this research is PT. Alphacon Valfindo in the period January 2016 to December 2016, with the sample used in this study is the data of steel scrap inventory costs of PT. Alphacon Valfindo in the period January 2016 to December 2016. The tool / instrument used is finding the optimal order for one order using the Economic Order Quantity (EOQ) method, and comparing the company's total actual inventory costs with the cost of inventory using the EOQ method.